Women Entrepreneurs and Changing Social Structure of KSA - Imran Saleem; Mohd. Yasir Arafat; Anjila Saleem (Vikalpa)
This study investigates factors that encourage and discourage women entrepreneurship in Saudi Arabia. The research uses the Adult Population Survey (APS) and analysed data collected from 1,305 women. Findings show that perceived capability, opportunity perception, risk perception, social network and informal investment significantly influence women’s propensity to entrepreneurship. However, the entrepreneurial propensity of women who have financed others’ businesses is negative. This study highlights the need for entrepreneurship researchers to examine factors that mobilize and inhibit entrepreneurial initiatives among women and study cognitive and social capital variables in an integrated framework.